An analysis of fabric recycling campaign kloth cares mask product poster / Nurshavareena Khalid, Azahar Harun and Liza Marziana Mohammad Noh - Khalid, Nurshavareena; Harun, Azahar; Mohammad Noh, Liza Marziana (Faculty of Art & Design, 2022)
In this globalized world, women also play an essential role in improving the economy. However, not everyone is lucky. Therefore, various initiatives are underway to bridge the economic gap for underprivileged women. The objective of this study is to analyze the element of visuals that had been applied in the Woman Up recycling campaign poster and to find what elements of the design represent women and fabric recycling in the poster campaign. There is much awareness of posters on recycling however, posters on recycling fabric waste and empowering women are tough to find. The contribution of this study will help the graphic designer to design artwork comprehensively by using these findings as a reference and impact the visual to capture more awareness for the audience besides supporting the campaign Women Up by Kloth Cares by a commitment to improving the livelihood of women from the vulnerable community. By using a visual approach, therefore three posters were taken and evaluated through Feldman Theory to propose visual arts criticism including Description, Analysis, Interpretation, and Judgment.